Upaya Edukasi Perilaku Anti Bullying Kepada Anak anak di Panti Asuhan Universal Anak Indonesia - Putri, Malida; Hutapea, Meidona (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
We cannot deny that nowadays, namely in the digital era, everything is very easy to obtain, be it negative or positive things, including children who are in their infancy, children in their infancy are very fast in receiving information, but in this case children in general cannot distinguish good or bad information, therefore as adults must be able to monitor and provide boundaries and understanding of good and bad things, there are many things that can make children affected by bad behavior, unlike bullying, pornography, or other delinquency, but in this case the author decided to raise the title according to the mini project, namely Anti-Bullying Behavior Education Efforts for Children of the Universal Children's Indonesian Orphanage, bearing in mind that children who live in orphanages are very vulnerable as victims of bullying or not even rule out the possibility of becoming a bully even in mini pro In this project, the authors created a mini project on this matter with various stages in accordance with social welfare science, the Intervention Program used in this Practicum activity was the group work method by zastrow which consisted of; Intake and contract, Assessment and Intervention Planning, selection of appropriate members age and development, Group Development, Evaluation and Termination